2004
DOI: 10.1021/jo048944k
|View full text |Cite
|
Sign up to set email alerts
|

New C−C Coupling Reaction of Cyclic Nitronates with Carbon Nucleophiles. Umpolung of the Conventional Reactivity of Nitronates

Abstract: Cyclic six-membered nitronates 1 are involved in diastereoselective C-C coupling reactions with various nucleophiles in the presence of either catalytic or stoichiometric amounts of TBDMSOTf to give the previously unknown N-siloxytetrahydrooxazines. The intermediacy of N,N-bis(oxy)iminium cations was proven by NMR data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…The structures of the isoxazolidines 5a-h were unambiguously confirmed by elemental analysis as well as by 1 H, 13 C, 29 Si NMR and 2D NMR spectroscopy (COSY, HSQC and NOESY). The isoxazolidines 5a-c,g,h were characterized as individual diastereomers, whereas the nitroso acetals 5d-f were analysed as mixtures of diastereomers (see Table 1).…”
Section: Structure Elucidation Of the Isoxazolidines 5a-hmentioning
confidence: 78%
See 4 more Smart Citations
“…The structures of the isoxazolidines 5a-h were unambiguously confirmed by elemental analysis as well as by 1 H, 13 C, 29 Si NMR and 2D NMR spectroscopy (COSY, HSQC and NOESY). The isoxazolidines 5a-c,g,h were characterized as individual diastereomers, whereas the nitroso acetals 5d-f were analysed as mixtures of diastereomers (see Table 1).…”
Section: Structure Elucidation Of the Isoxazolidines 5a-hmentioning
confidence: 78%
“…It was found that the workup procedure previously used for six-membered nitronates [1,2] (procedure Table 1. C-C coupling reactions of five-membered cyclic nitronates 3 with silyl ketene acetal 4.…”
Section: Addition Of Silyl Ketene Acetal 4 To Nitronates 3a-hmentioning
confidence: 99%
See 3 more Smart Citations